Effect of Leadership and Work Stress on Employee Performance at The Transportation Office of Cirebon Regency - Damdam Damiyana; Nurdin; Sandi Nasrudin Wibowo; Irfan Maulana (PT Mattawang Mediatama Solution, 2022)
This study aims to determine the effect of leadership and work stress partially or indirectly on employee performance at the Cirebon Regency Transportation Office. The population used in this study were employees of the Cirebon Regency Transportation Service. The sampling technique in this study used a sample of propotionate stratified random sampling totaling 60 respondents. Methods in collecting data using a questionnaire. Assumption test uses normality test and multicollinearity test. Regression test using multiple linear regression analysis. The coefficient of determination test is used to determine the percentage change in the dependent variable (Y) caused by the independent variable (X). Hypothesis testing using t and f tests. The results of this study conclude that (1) Leadership has a significant and positive effect on employee performance seen from the value of t count > t table, namely 3.481 > 1.671. (2) Job stress has a significant and significant effect on employee performance seen from the value of tcount > ttable, which is 3,266 > 1,671. (3) Leadership and work stress have a significant effect on employee performance as seen from the value of Fcount > Ftable, which is 8.008 > 3.16. All research results either partially or simultaneously have sig values < 0.05 or 0.000 < 0.05. (3) Leadership and work stress have a significant effect on employee performance as seen from the value of Fcount > Ftable, which is 8.008 > 3.16. All research results either partially or simultaneously have sig values < 0.05 or 0.000 < 0.05. (3) Leadership and work stress have a significant effect on employee performance as seen from the value of Fcount > Ftable, which is 8.008 > 3.16. All research results either partially or simultaneously have sig values < 0.05 or 0.000 < 0.05.